Violence against psychiatric trainees from Asian countries: A pilot online survey - Arpit Parmar; Sundar Gnanavel; Ahmet Gürcan; Yugesh Rai; Utkarsh Karki; Mariana Pinto da Costa; Anna Szczegielniak; Victor Pereira-Sanchez (Indian Journal of Psychiatry)
Background: Violence against psychiatry trainees is an important issue to the medical profession. However, this matter has been under researched, especially in Asian countries. Aim: We aimed to explore the rates and factors associated with violence against psychiatric trainees in Asian countries. Methods: An online, 15 item cross sectional pilot survey was designed and disseminated among psychiatric trainees in Asia through the World Network of Psychiatric Trainees, national and local networks of trainees, and social media. The questionnaire sought to enquire about the experience of physical, verbal, and sexual assaults and its impact. Data were analyzed using Statistical Package for the Social Sciences (SPSS) V20.0. Results: A total of 467 responses were obtained from psychiatric trainees in 16 countries in Asia. More than two thirds of participants (n = 325, 69.59%) reported a history of assault. Psychiatry inpatient units were the most common setting (n = 239, 73.54%). A relatively lower proportion of participants from the East Asian countries reported an assault, compared to other countries (χ2 = 13.41, P = 0.001). Sexual assault was more common among women compared to men (χ2 = 0.94, P = 0.002). Conclusion: Violence against psychiatric trainees seems common across Asian countries. Our findings call for further systematic investigation of the phenomenon and suggest the need to develop programs to protect psychiatric trainees against the threat of violence and its subsequent psychological complications.